Promising New Tools for Targeting p53 Mutant Cancers: Humoral and Cell-Based Immunotherapies - Chasov, Vitaly; Zaripov, Mikhail; Mirgayazova, Regina; Khadiullina, Raniya; Zmievskaya, Ekaterina; Ganeeva, Irina; Valiullina, Aigul; Rizvanov, Albert; Bulatov, Emil (Frontiers in Immunology, 2021)
Transcription factor and oncosuppressor protein p53 is considered to be one of the most promising molecular targets that remains a high-hanging fruit in cancer therapy. TP53 gene encoding the p53 protein is known to be the most frequently mutated gene in human cancers. The loss of transcriptional functions caused by mutations in the p53 protein leads to deactivation of intrinsic tumor suppressive responses associated with wild-type (WT) p53 and acquisition of new pro-oncogenic properties such as enhanced cell proliferation, metastasis and chemoresistance. Hotspot mutations of p53 are often immunogenic and elicit intratumoral T cell responses to mutant p53 neoantigens, thus suggesting this protein as an attractive candidate for evaluating targeted anti-cancer immunotherapies. In this review we discuss the possible use of p53 antigens as molecular targets in immunotherapy including the application of T cell receptor mimic (TCRm) monoclonal antibodies (mAbs) as a novel powerful approach.